Dlhawksworthia flavoparmeliae sp. nov., a new endolichenic fungus in Phaeosphaeriaceae - Si, Hong-Li; Zheng, Xiao-Xiao; Li, Xin-Chao; Su, Yue-Min; Bose, Tanay; Chang, Run-Lei (Phytotaxa, 2021)
The genus Dlhawksworthia presently includes three species. All the previously described species have been isolated from plants. Besides, none of these three species have ever been recorded in China. We conducted surveys in various regions of China to isolate and identify endolichenic fungi associated with diverse lichen species. During these surveys, we isolated both previously known and undescribed fungi associated with lichens. Among these, there was an isolate of an unknown fungus. The morphological and molecular analyses indicated that this isolate represented a new species from the genus Dlhawksworthia. As a consequence, we described this fungus as Dlhawksworthia flavoparmeliae sp. nov. This is the first report of Dlhawksworthia isolated from a lichen in China and globally.